Inhibition of atypical protein kinase Cι induces apoptosis through autophagic degradation of β‐catenin in esophageal cancer cells. Issue 7 (28th January 2013) - Wang, Bo‐Shi; Yang, Yang; Lu, Hai‐Zhen; Shang, Li; Zhang, Yu; Hao, Jia‐Jie; Shi, Zhi‐Zhou; Wang, Xiao‐Min; Liu, Yi‐Zhen; Zhan, Qi‐Min; Jia, Xue‐Mei; Wang, Ming‐Rong
Abstract Atypical protein kinase Cι (PKCι) has been identified as an oncoprotein in esophageal squamous cell carcinomas. However, the mechanisms underlying the role of PKCι in this disease remain unclear. In the present work, we found that inhibition of PKCι expression by RNAi induced apoptosis via the down‐regulation of β‐catenin in esophageal cancer cells. Furthermore, we found that PKCι regulated β‐catenin in an autophagy dependent way. Since down‐regulation of β‐catenin induced by knockdown of PKCι could be rescued by autophagy inhibition; knockdown of PKCι activated autophagy and promoted the recruitment of β‐catenin into autophagosome. These results suggested that PKCι positively regulated β‐catenin through negatively regulated autophagy and depletion of PKCι promoted apoptosis via autophagic degradation of β‐catenin in esophageal cancer cells. These data provide new insights into PKCι signaling in human cancer. © 2013 Wiley Periodicals, Inc.